2021
DOI: 10.1001/jamanetworkopen.2021.25063
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Emergency Department Encounters for Vomiting After Cannabis Legalization in Colorado

Abstract: Key Points Question Has the number of vomiting-related emergency department visits increased after recreational cannabis legalization in Colorado? Findings In this cross-sectional study of 820 778 patients seeking care through Colorado emergency departments, cannabis legalization was associated with an increase in annual vomiting-related health care encounters. The highest increases were observed in counties without existing medical dispensaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 33 publications
4
26
0
Order By: Relevance
“…While prior studies have broadly found that legalization is associated with increases in CHS presentations, our results suggest that regulatory approaches may influence these changes. 9 , 10 , 11 , 12 We found that legalization with strict controls over retail store access and product type was not associated with large changes in CHS. In contrast, allowing the commercialization of recreational cannabis may be associated with substantial increases in heavy and regular cannabis use, leading to CHS.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…While prior studies have broadly found that legalization is associated with increases in CHS presentations, our results suggest that regulatory approaches may influence these changes. 9 , 10 , 11 , 12 We found that legalization with strict controls over retail store access and product type was not associated with large changes in CHS. In contrast, allowing the commercialization of recreational cannabis may be associated with substantial increases in heavy and regular cannabis use, leading to CHS.…”
Section: Discussionmentioning
confidence: 76%
“…First, there is currently no diagnostic code for CHS, and our study infers CHS from a combination of diagnostic codes previously used in the literature. 9 , 10 Importantly, the specificity and sensitivity of this coding combination are currently unknown, and our study may underestimate the burden of CHS, which is often not considered as a cause of vomiting in ED visits. 19 Second, the observed increases could be from a greater awareness of CHS by ED physicians or the willingness of patients to disclose cannabis use.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…10 CHS remains a poorly studied disorder, with very little data available globally on incidence trends. Increased emergency department visits for vomiting in the US 12 and France, 13 as well as anecdotal clinical impressions from the authors' gastroenterology and emergency medicine practices suggest the prevalence may be widespread. Conversely, a questionnaire-based study from North America and the UK suggests that CHS is uncommon when strict Rome IV criteria are used.…”
Section: Introductionmentioning
confidence: 88%
“…Some of the consultation calls were seeking treatment advice for cannabis hyperemesis syndrome or acute psychotic reactions, two acute medical problems related to cannabis use. These problems are increasing in frequency ( 17 , 18 ) in association with policy changes that liberalize access to cannabis in Massachusetts and other states, and with increasing potency and variety of products available. These acute problems may cause patients to seek medical attention, and thereby shine a light on substance use in general for pediatric primary care providers.…”
Section: Discussionmentioning
confidence: 99%